A Cross-Sectional Study on Pattern and Injury Severity Score in Thoracoabdominal Trauma Among Medicolegal Autopsy Cases in North India - Jasbir Singh (Asian Journal of Medical Research, 2022)
Background: The World Health Organization defines an accident as an unanticipated, unplanned event that may result in injury. A post-mortem investigation of the Injury Severity Score (ISS) can reveal what types of injuries are life-threatening as well as their severity, so this study    was carried out to determine the pattern of thoraco-abdominal injuries and period of survival, with a special focus on Injury Severity Score (ISS). Subjects and Methods: This cross-sectional study was carried for a duration of two years in a Hospital of Delhi, India among 231 cases of thoraco-abdominal injuries brought for medico-legal autopsies. Post-mortem examination was carried out to record external and internal findings on the body, and Injury severity score (ISS) was derived for the injuries. All tests were performed at a 5% level of significance; thus, an association was significant if the p value was less than 0.05. Results: The most usually impacted age group was 31-40 years (31.2%). Road traffic accidents (71.4%) were the most common mode of injury in the current study. Half of the victims (55.8%) died in hospital, and haemorrhagic shock was the cause of death in 33.9% of the victims. The rib fractures accounted for 75.3% of total visceral injuries. The Spearman Correlation analysis showed as the Injury Severity Score (ISS) increases, the survival time decreases significantly. Conclusion : According to the findings of this study, the most prevalent cause of thoraco-abdominal trauma is a road traffic accident and victims with a low ISS had a longer survival period than those with a higher ISS.